The regionalization of a university project of educational robotics to help Costa Rican youth to avoid drug consumption - Fonseca Solano, Pedro (2019)
The following article presents the experience of the regionalization of the Training of Trainers in Robotics project in Schools in vulnerable areas of Costa Rica to the different regions outside the Greater Metropolitan Area. This in order to have a presence throughout the national territory and be able to train more secondary teachers in the area of educational robotics. And that they so that these favored by means of access to technology that allows them to solve problems that involve the design, construction and programming of robotic models; also that they take advantage of free time in the study of this technology. © 2019 IEEE.